2008
DOI: 10.1158/1535-7163.mct-07-2118
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of sonic hedgehog-GLI signaling: a potential strategy to improve therapy for mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) has one of the worst clinical outcomes among the B-cell lymphomas, with a median survival of only 3 to 4 years. Therefore, a better understanding of the underlying mechanisms that regulate MCL proliferation/survival is needed to develop an effective therapy. Because sonic hedgehog (Shh)-GLI signaling has been shown to be important in the proliferation and survival of several cancers, and no such information is available for MCL, this study was undertaken. Our results show that the mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 39 publications
1
64
0
Order By: Relevance
“…Furthermore, downregulation of GLI transcription factors with the use of antisense oligonucleotides significantly reduced cyclin D1 and BCL-2 transcript levels, decreased proliferation of MCL cells, and increased their susceptibility to chemotherapy. 96 These results indicate a role for SHH-GLI signaling in MCL proliferation and identify the hedgehog pathway as a potential therapeutic target in MCL Antiapoptotic BCL-2 family proteins BCL-2 family proteins are key regulators of apoptosis, determining cellular fate in response to numerous insults ( Figure 6). 97 The BCL-2 pathway is deregulated in MCL; high-level copy number gains of the BCL2 locus at 18q21.3 are frequent, 31 high MCL1 expression is common in more aggressive tumors 98 and can be increased by AKT/mTOR signaling, and BCL-X L overexpression has been linked to constitutive activation of the NF-B pathway.…”
Section: Hedgehog Pathwaymentioning
confidence: 85%
“…Furthermore, downregulation of GLI transcription factors with the use of antisense oligonucleotides significantly reduced cyclin D1 and BCL-2 transcript levels, decreased proliferation of MCL cells, and increased their susceptibility to chemotherapy. 96 These results indicate a role for SHH-GLI signaling in MCL proliferation and identify the hedgehog pathway as a potential therapeutic target in MCL Antiapoptotic BCL-2 family proteins BCL-2 family proteins are key regulators of apoptosis, determining cellular fate in response to numerous insults ( Figure 6). 97 The BCL-2 pathway is deregulated in MCL; high-level copy number gains of the BCL2 locus at 18q21.3 are frequent, 31 high MCL1 expression is common in more aggressive tumors 98 and can be increased by AKT/mTOR signaling, and BCL-X L overexpression has been linked to constitutive activation of the NF-B pathway.…”
Section: Hedgehog Pathwaymentioning
confidence: 85%
“…Active paracrine Hedgehog signaling has been shown in other B-cell malignancies (30,31). Hedgehog pathway components are present in Burkitt lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…12,94 In mantle cell lymphoma, preliminary work has shown that mantle cell lymphoma cell lines and primary human samples had increased expression of Hh pathway components compared with normal B cells and were partially responsive to HH ligand or its pharmacologic inhibition. 95 Direct inhibition of the downstream effectors GLI1 and GLI2 had the most profound effect on mantle cell lymphoma cells, indicating that, although canonical Hh signaling may be involved in mantle cell lymphoma, there are probably other factors driving GLI1 and GLI2 expression.…”
Section: Lymphoma and Cllmentioning
confidence: 97%